DIAGNOSTIC VALUE OF CHANGES FATTY ACIDS COMPOSITION IN BLOOD PLASMA AND ERYTHROCYTES PATIENTS WITH FIBROUS -CAVERNOUS PULMONARY TUBERCULOSIS, NOT SUFFERED FROM THE CHERNOBYL CONSEQUENCES, COMPARATIVE ANALYSIS OF THEIR INDICATORS - Пікас, О.Б. (World of Medicine and Biology, 2015)
The studies were aimed at investigating and evaluating peculiar features of changes composition of fatty acids of lipids plasma and blood erythrocytes in suffering from fibrous-cavernous pulmonary tuberculosis (unaffected by the consequences of the Chernobyl accident). Materials and methods. Were examined 103 (53,9 % out of 191) healthy people (І group) and 57 (46,1 % out of 191) patients with fibrous-cavernous pulmonary tuberculosis, unaffected by the consequences of the Chernobyl accident (ІІ group). Fatty-acid composition of lipids plasma and blood erythrocytes to study by the biochemical method using а gas-liquid chromatography “Cvet – 500”.Results and discussion. The results obtained showed disorders in metabolism of higher fatty acids of lipids plasma and blood erythrocytes in suffering from fibrous-cavernous pulmonary tuberculosis, unaffected by the consequences of the Chernobyl accident. In both healthy persons composition of fatty acids of lipids demonstrated unidirectional in lipids plasma and blood erythrocytes. In patients with fibrous-cavernous pulmonary tuberculosis, unaffected by the consequences of the Chernobyl accident, composition of fatty acids demonstrated unidirectional changes in their ratio both of lipids plasma and blood erythrocytes: we noted а significant elevation in total saturated fatty acid at the expense against а background of an reduction in total unsaturated fatty acids as well and total polyunsaturated fatty acid contents. In plasma and blood erythrocytes of patients with fibrous-cavernous pulmonary tuberculosis, unaffected by the consequences of the Chernobyl accident, was recorded decrease in the number of palmitic (C16:0), stearic (C18:0), oleic (C18:1) and linoleic (C18:2) fatty acids, set the appearance of myristic (C14:0), pentadecanoic (C15:0), margarine (C17:0) and eicosatrienoic (C20:3) fatty acids. In patients with fibrous-cavernous pulmonary tuberculosis diverse set of changes in arachidonic fatty acid (C20:4): in biological membranes of erythrocytes content was reduced (to (2,0 ± 0,5) % (p < 0,001) at (13,9 ± 0,7) % in healthy individuals), in plasma - increased (to (6,8 ± 0,8) % (p < 0,001) with (3,9 ± 0,4) % in healthy subjects).Conclusions. A comparative analysis of individual fatty acid contents, total saturated fatty acid contents, total unsaturated fatty acid contents and total polyunsaturated fatty acid contents of lipids plasma and blood erythrocytes іn patients with fibrous-cavernous pulmonary tuberculosis, unaffected by the consequences of the Chernobyl accident, determines the greater sensitivity of erythrocytes to lipid per oxidation and indicates а possible better use of erythrocytes of blood for the study of lipid metabolism.
Keywords: composition of fatty acids; plasma; blood erythrocytes fibrous-cavernous pulmonary tuberculosis